2022
DOI: 10.3390/buildings12020220
|View full text |Cite
|
Sign up to set email alerts
|

Circular Building Process: Reuse of Insulators from Construction and Demolition Waste to Produce Lime Mortars

Abstract: This research aims to revalue the possibilities presented by lime mortars for use in renovation and as cladding material on facades. The study focuses on analyzing the technical feasibility of lime mortars with the incorporation of residues from three types of thermal insulation materials: expanded polystyrene with graphite especially suitable for use on facades; expanded polystyrene for use indoors; and insulating mineral wool. The incorporation of these construction and demolition residues makes it possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 64 publications
0
3
0
1
Order By: Relevance
“…This is drinking water fit for human consumption and suitable for use in mortars and concretes [58], which has been successfully used in previous studies [59]. Among its main characteristics are its soft hardness (25 mg CaCO 3 /L) and neutral pH between 7 and 8 [60] recommended to avoid setting alterations.…”
Section: Mortars Elaborationmentioning
confidence: 99%
“…This is drinking water fit for human consumption and suitable for use in mortars and concretes [58], which has been successfully used in previous studies [59]. Among its main characteristics are its soft hardness (25 mg CaCO 3 /L) and neutral pH between 7 and 8 [60] recommended to avoid setting alterations.…”
Section: Mortars Elaborationmentioning
confidence: 99%
“…Já Santos e Cabral (2020) considerou, em seus estudos, a substituição da areia natural por agregados produzidos através da reutilização de RCD, em proporções de 25% e 50%, encontrando resultados promissores quanto às características físicas e a resistência mecânica em traços de emboço e contrapiso. Ferrández et al (2022) propõem o uso de RCD para a produção de argamassas para uso em reformas e em revestimentos de fachada. Os autores encontraram resultados robustos quanto às propriedades físicas e mecânicas do material final obtido e concluem que a incorporação do RCD é viável tecnicamente e melhora o desempenho das argamassas de cal para as finalidades estudadas.…”
Section: Resultsunclassified
“…Improving the dimensional stability of mortars by reducing shrinkage is shown as well [30]. In this way, through simulations using software such as STAR-CCM+©, Piña et al [32] demonstrated that the energy efficiency of buildings incorporating mortar coatings with mineral wool fiber additions can be improved. In addition, in previous studies, it has been observed that the incorporation of mineral wool residues in plaster mortars increases the mechanical strength of prefabricated slabs and panels [33].…”
Section: Introductionmentioning
confidence: 98%